2021
DOI: 10.3389/fcell.2020.610903
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-angiogenesis in the Treatment Landscape of Non-small Cell Lung Cancer – New Combinational Approaches and Strategies of Neovessel Inhibition

Abstract: Tumor progression depends primarily on vascular supply, which is facilitated by angiogenic activity within the malignant tissue. Non-small cell lung cancer (NSCLC) is a highly vascularized tumor, and inhibition of angiogenesis was projected to be a promising therapeutic approach. Over a decade ago, the first anti-angiogenic agents were approved for advanced stage NSCLC patients, however, they only produced a marginal clinical benefit. Explanations why anti-angiogenic therapies only show modest effects include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 143 publications
0
33
0
1
Order By: Relevance
“…HEVs in TLSs are associated with T and B cell infiltration and indicate favorable outcomes in oral carcinoma and breast cancer ( 72 , 73 ). The emergence of HEVs also contributes to the formation of TLSs ( 74 ). There is ample evidence that the function of HEVs in TLSs is similar to that in LNs, providing a channel for immune cells to accumulate in the tumor.…”
Section: The Function Of Tlss In the Tmementioning
confidence: 99%
“…HEVs in TLSs are associated with T and B cell infiltration and indicate favorable outcomes in oral carcinoma and breast cancer ( 72 , 73 ). The emergence of HEVs also contributes to the formation of TLSs ( 74 ). There is ample evidence that the function of HEVs in TLSs is similar to that in LNs, providing a channel for immune cells to accumulate in the tumor.…”
Section: The Function Of Tlss In the Tmementioning
confidence: 99%
“… 6 Angiogenesis is closely related to tumor progression and it makes tumors more prone to metastasis and recurrence; thus, highly vascularized NSCLC tends to be associated with a poor prognosis. 5 , 7 Currently, microvessel density (MVD) is the most commonly used indicator to evaluate angiogenesis. 8 In vasculogenic mimicry (VM), a tube surrounded by tumor cells lined with a periodic acid-Schiff (PAS)-positive basement membrane is formed.…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC is a highly vascularized tumor and inhibition of angiogenesis has become a promising therapeutic approach [ 7 ]. It is reported that vascular endothelial growth factor (VEGF) plays an important role in the angiogenic signaling and vascular endothelial growth factor receptors (VEGFRs) are tyrosine kinases that serve as key regulators of this process.…”
Section: Introductionmentioning
confidence: 99%